2007
DOI: 10.2139/ssrn.1329310
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Pricing and Reimbursement Policies in Sweden

Abstract: This paper examines aspects of the policy environment and market characteristics of the Swedish pharmaceutical sector, assesses the degree to which Sweden has achieved certain policy goals, and puts forth some key findings and conclusions. Thanks to low markups in the distribution chain and no VAT for prescribed medicines, Sweden's public prices for pharmaceuticals are relatively low, in contrast to average prices received by manufacturers, which are among the highest in Europe. Recent reforms have helped to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 35 publications
0
19
0
11
Order By: Relevance
“…The outcome was pharmaceutical accessibility, as measured by two proxies, namely the number of pharmacies per 1000 inhabitants (Ph/inhab) and the number of pharmacies per km 2 (Ph/km 2 ) (Moïse and Docteur, 2007).…”
Section: Study Variables and Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome was pharmaceutical accessibility, as measured by two proxies, namely the number of pharmacies per 1000 inhabitants (Ph/inhab) and the number of pharmacies per km 2 (Ph/km 2 ) (Moïse and Docteur, 2007).…”
Section: Study Variables and Data Sourcesmentioning
confidence: 99%
“…This implies that many people do not access the closest pharmacy, perhaps owing to inconvenient opening hours, personal preferences or financial issues. Secondly, although it has been suggested that analysing potential accessibility to pharmacies at the municipal level and focusing on remote areas may be optimal (Moïse and Docteur, 2007), the minimum local level in Italy is, theoretically, the census tract. Indeed, dividing large municipalities with this in mind would provide useful, more detailed information.…”
Section: Deregulation and Spatial Accessibility To Community Pharmaciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of pharmaceuticals increased significantly in Sweden during the 1990s [4,5], and this rate of increase was relatively faster than that of other components of the healthcare system. This trend has continued, and in 2006, pharmaceuticals accounted for approximately 11.6% of the total healthcare expenditure [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This trend has continued, and in 2006, pharmaceuticals accounted for approximately 11.6% of the total healthcare expenditure [5,6]. Expenditure is expected to continue growing at approximately 4% annually during the upcoming years [6,7].…”
Section: Introductionmentioning
confidence: 99%